Impact of Comorbidities on Beneficial Effect of Lactated Ringers vs. Saline in Sepsis Patients - Tseng, Chien-Hua; Chen, Tzu-Tao; Chan, Ming-Cheng; Chen, Kuan-Yuan; Wu, Sheng-Ming; Shih, Ming-Chieh; Tu, Yu-Kang (Frontiers in Medicine, 2021)
Background: Lactated Ringers reduced mortality more than saline in sepsis patients but increased mortality more than saline in traumatic brain injury patients. Method: This prospective cohort study was conducted in a medical intensive care unit (ICU) in central Taiwan from Jan 2015 through Dec 2017. We applied standard sepsis evaluation protocol and identified heart, lung, liver, kidney, and endocrine comorbidities. We also evaluated resuscitation response with central venous pressure, central venous oxygen saturation, and serum lactate level simultaneously. Propensity-score matching and Cox regression were used to estimate mortality. The competing risk model compared the lengths of ICU and hospital stays with the subdistribution hazard ratio (SHR). Mixed-effect linear model and interaction terms were used to analyze changes in clinical variables. Results: Overall, 938 patients were included in the analysis. The lactated Ringers group had a lower mortality rate (adjusted hazard ratio, 0.59; 95% CI 0.43-0.81) and shorter lengths of hospital stay (SHR, 1.39; 95% C.I. 1.15-1.67) than the saline group; the differences were greater in patients with chronic pulmonary disease and small and nonsignificant in those with chronic kidney disease, moderate to severe liver disease and cerebral vascular disease. The resuscitation efficacy was the same between fluid types, but serum lactate levels were significantly higher in the lactated Ringers group than in the saline group (0.12 mg/dL/hour; 95% C.I.: 0.03, 0.21), especially in chronic liver disease patients. Compared to the saline group, the lactated Ringers group achieved target glucose level earlier in both diabetes and non-diabetes patients. The serum potassium level increased within the first few hours and recovered more slowly in patients with chronic kidney disease regardless of fluid type. Conclusion: Lactate Ringer’s solution provides greater benefits to patients with chronic pulmonary disease than to those with chronic kidney disease, or with moderate to severe liver disease. Comorbidities are important in choosing resuscitation fluid types.